Pro spatial with SQL server 2012 - Aitchison, Alastair (Expert's voice in databases., 2012)
Microsoft SQL Server implements extensive support for location-based data. Pro Spatial with SQL Server 2012 introduces SQL Server's spatial feature set, and covers everything you'll need to know to store, manipulate, and analyze information about the physical location of objects in space. You'll learn about the geography and geometry datatypes, and how to apply them in practical situations involving the spatial relationships of people, places, and things on Earth. Author Alastair Aitchison first introduces you to SQL Server's spatial feature set and the fundamental concepts involved in working with spatial data, including spatial references and co-ordinate systems. You'll learn to query, analyze, and interpret spatial data using tools such as Bing Maps and SQL Server Reporting Services. Throughout, you'll find helpful code examples that you can adopt and extend as a basis for your own projects. Explains spatial concepts from the ground up--no prior knowledge is necessary Provides comprehensive guidance for every stage of working with spatial data, from importing through cleansing and storing, to querying, and finally for retrieval and display of spatial data in an application layer Brilliantly illustrated with code examples that run in SQL Server 2012, that you can adapt and use as the basis for your own projects.